The Economic Structure of Roman Cities in Ancient North Africa (Al-Farooq Journal of Sciences, 2026)
This research aims to analyze the economic and social life in Roman cities in the ancient Maghreb, understanding how these cities were integrated into the Roman Imperial economy and the impact of economic activity on urban and social structures. It also examines the interaction between local heritage and the Roman urban model. Furthermore, the study seeks to highlight the role of cities within the Mediterranean production, distribution, and trade systems, and to explore how agricultural resources and artisanal industries contributed to enhancing the local economy and linking it with major imperial markets.The research adopts a descriptive-analytical approach, combining the analysis of archaeological sources—such as sites, urban layouts, ports, and industrial workshops—with classical and historical texts. It also utilizes a comparative method to study the influence of the Roman model on the local economic and social fabric. Economic, political, religious, and cultural data are integrated to provide a comprehensive vision of Roman city life in the region.The results indicate that Roman cities functioned as integrated economic centers, where markets, warehouses, ports, and industrial workshops were systematically linked to support production, consumption, and trade. These cities played a vital role in supplying Rome with grain and olive oil, while artisanal industries added significant value to local resources. Economic activity was reflected in the social and urban structure through the development of municipal councils, temples, and recreational facilities, which fostered interaction among inhabitants and consolidated Roman values while preserving local specificities. These cities emerged as active urban poles in the Mediterranean basin, making them a key to understanding the social, political, and economic transformations in the ancient Maghreb during the Roman era.